The Instruments Measuring Nurses’ Posttraumatic Growth During the Covid-19 Pandemic: A Scoping Review - Handoko, Yudho Tri; Asmaningrum, Nurfika; Ardiana, Anisah (Indonesian Journal of Global Health Research, 2024)
Posttraumatic growth (PTG) refers to positive psychological changes that occur in individuals who have experienced traumatic events, such as nurses battling an underpressure situation during the COVID-19 pandemic. The attempts at measuring PTG are still limited due to the lack of instruments that suit natural variations caused by culture or language adaptation and sampling types. Although there are many studies regarding PTG, no comprehensive review has been found to identify the instrument measuring nurses' posttraumatic growth. Objective: The study aimed to identify research on instruments measuring nurses’ PTG during the COVID-19 pandemic. Method: Five online databases (PubMed, Wiley Online Library, Proquest, Science Direct, and Google Scholar) were put under analysis to identify studies that report information on instruments measuring nurses’ PTG. Only studies published between 2020-2024 were involved in the analysis. The selection process was done using Preferred Reporting Items for Systematic Reviews (PRISMA). Results: From the identification process, authors found 6,589 articles and after going through the screening and eligibility stages 24 studies were included in this review. Exploring PTG among nurses involves examining how they reflect upon and derive meaning from their experiences during challenging circumstances. Several instruments to measure PTG among nurses were identified, inter alia, Posttraumatic Growth Inventory (PTGI), Posttraumatic Growth Inventory Chinese versions (PTGI-C), Posttraumatic Growth Inventory-Expanded (PTGI-X), Posttraumatic Growth Inventory-Short Form (PTGI-SF), and Turkish, Polish, and Korean versions of PTGI. Conclusion: In general, the original version of PTGI has been adapted and translated into several languages to measure PTG among nurses during the COVID outbreak.